KUALITAS JASA PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI PUSKESMAS LANCIRANG KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Mardiana Mardiana (JIA: Jurnal Ilmiah Administrasi, 2020)
Abstract This study aims to determine the quality of service to inpatient satisfaction and the factors that influence the quality of service to inpatient satisfaction at the Lancirang Health Center, Pitu Riawa District, Sidenreng Rappang Regency. The population of this study was 1,594 people and a sample of 94 inhabitants. The sampling technique used is Purpossive Sampling. This type of research is quantitative descriptive. Data collection techniques are observation, interviews, library research and questionnaires. Data analysis techniques use statistics. The results showed that the service quality with an average percentage of 58% less satisfied, consisting of tangibles (physical evidence) 75% satisfied, reliability (reliability) 54% less satisfied, responsiveness (responsiveness) 47% less satisfied, assurance (guarantee) 58% less satisfied, empathy (empathy) 58% less satisfied. Patient satisfaction with an average percentage of 66% satisfied, consisting of the attitude of the staff approach to patients 54% less satisfied, the quality of care received by patients 53% less satisfied, administrative procedures 62% satisfied, waiting time 78% satisfied, other public facilities 85% are very satisfied, inpatient facilities 75% satisfied and the results of treatment or treatment received by patients 55% less satisfied. Factors that influence the quality of services to inpatient satisfaction at the Lancirang Health Center, Pitu Riawa District, Sidenreng Rappang Regency are expected services and services received by 51% less satisfied. Keywords: Community Satisfaction and Quality of Service